2023
DOI: 10.3390/toxics11050415
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Risk Assessment of PAH Pollution in Soil of a Retired Coking Wastewater Treatment Plant in Taiyuan, Northern China

Abstract: We analyzed the soil at the site of a former coking wastewater treatment plant on redeveloped land in Taiyuan, northern China, in an attempt to detect the presence of 16 types of priority polycyclic aromatic hydrocarbons (PAHs) listed by the United States Environmental Protection Agency (US EPA) and evaluate the potential pollution risks. The results show that the total proportion of PAHs in the surface soil of the redeveloped land ranged from 0.3 to 1092.57 mg/kg, with an average value of 218.5 mg/kg, mainly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…Figure S7 showed that particles were apt to distribute in fine size in both HFO and EHFO exhausts. This distribution consisted with typical nucleation patterns in combustion exhausts [ 60 ], including real-world ship engine exhausts [ 61 , 62 ]. Compared to HFO, although the total EF PM was reduced, the emissions of fine particles ( D P < 0.65 μm) were enhanced by burning EHFO, especially at 50% and 75% loads, which might pose a higher risk of inhalation of exhausted particles (without concerning the toxicity of individual particle herein).…”
Section: Resultsmentioning
confidence: 99%
“…Figure S7 showed that particles were apt to distribute in fine size in both HFO and EHFO exhausts. This distribution consisted with typical nucleation patterns in combustion exhausts [ 60 ], including real-world ship engine exhausts [ 61 , 62 ]. Compared to HFO, although the total EF PM was reduced, the emissions of fine particles ( D P < 0.65 μm) were enhanced by burning EHFO, especially at 50% and 75% loads, which might pose a higher risk of inhalation of exhausted particles (without concerning the toxicity of individual particle herein).…”
Section: Resultsmentioning
confidence: 99%